Stromatolites, so what?! A tribute to Robert N. Ginsburg. (4th June 2019) - Suosaari, Erica P.; Reid, R. Pamela; Andres, Miriam S.
Abstract: In tribute to Dr. Robert N. Ginsburg (1925–2017), we examine his 1991 seminal paper Controversies about Stromatolites: Vices and Virtues, which summarized current ideas about stromatolites including controversies of definition, whether ancient stromatolites should be interpreted as sedimentary structures and mechanisms of carbonate fixation. The accepted model of stromatolite morphogenesis in 1991 was that biology controls microscale internal structure whereas environment controls macroscale morphology. Ginsburg, however, predicted that biology and environmental influences on stromatolite growth were closely coupled at macro, meso and micro scales. Recent research in Hamelin Pool and the Bahamas has advanced our understanding of the inherent duality of stromatolites and associated controversies. These studies suggest that at the macroscale, when physical forces are strong, the environment is the main control on the morphology; however, when physical forces are weak, biological communities become the main drivers of morphology. Therefore, stromatolites can be considered both as fossils and as sedimentary structures dependent on the energy in the environment of deposition. At the mesoscale, as predicted by Trompette, stromatolite fabrics are influenced equally by environment and biology. As the degree of lamination is often unknown or heterogeneous, a generic genetic term such as 'microbialite' is considered the most appropriate terminology for structures of probable microbial origin. At the microscale, stromatolite microfabrics reflect environmentally driven cycling of microbial communities, reflecting both biology and environment. With respect to carbonate fixation, research on modern stromatolites provides a model for biofilm precipitation of micritic laminae lacking microfossils in ancient stromatolites. As pointed out by Ginsburg, the inherent duality of environmental and biological controls of morphogenesis at all scales is at the root of many long‐standing controversies. Recent investigations corroborate the foresight of Ginsburg nearly 30 years ago, further confirming well‐preserved stromatolites can provide insight into both biology and environmental factors in ancient ecosystems. Abstract : In his 1991 paper, Controversies about Stromatolites: Vices and Virtues, Robert Ginsburg boldly predicted that biology and environmental influences on stromatolite growth were closely coupled in stromatolite morphogenesis. This paper uses recent research from Hamelin Pool and the Bahamas to confirm the prophetic nature of Ginsburg's comment made nearly 30 years ago, revealing that biology and environmental influences on stromatolite growth are closely coupled at macro, meso and micro scales.